The social expectations of Anglican clergy in England and Australia, 1850-1910 - Nicholls, P (1988)
﻿ In the early nineteenth century, the ideal type of Anglican parish clergyman was a member of a gentlemanly profession. Although he had few formal duties, he exercised a benevolent influence in a small, deferential community. His liberal education, independent income and ample leisure enabled him to pursue scholarly hobbies. In every English village, he was a light of civilization. The parson was spiritual half-brother of the squire, and the Church as a whole was closely identified with the landed classes in the social rank, governing role (the magistracy) and political sympathies of the parochial clergy. Urbanisation was the main force that largely destroyed the authenticity of this ideal. As society became horizontally divided, the power of locality dwindled. The Church's opponents - sceptics, Dissenters and organised labour - gained confidence. Rival authorities (to the pulpit) overwhelmingly established themselves in popular favour - especially the mass circulating press. The franchise was extended to the working classes, or at least to the aristocracy of labour with whom the Church of England had rarely felt easy. Finally, two of the props of the old ideal were knocked away - the prosperity of the agricultural sector, and the acceptance of the clergyman's calling as a learned profession. In Australia, there were similar problems for the Anglican minister, although most were in a more intense form. A lack of endowment, the prevailing democratic and anti-clerical sentiment in much of the political debate, and the high degree of geographical and social mobility characteristic of much of the colonial population, made the problems of the Church and of her parochial ministers appear overwhelming. The result was the development of a form of careerism in the clerical order that seemed to some censorious contemporaries to have been not merely improper but quite destructive of the ideal of the parish priest, an ideal which was still upheld despite its manifest inappropriateness.